Ultrasound assessment of gastric antrum in term pregnant women before elective cesarean section - Caio Klippel Amaral; Márcio Luiz Benevides; Marília Marquioreto Benevides; Diogo Leite Sampaio; Cor Jesus Fernandes Fontes (Brazilian Journal of Anesthesiology, 2019)
Background and objectives: Pregnant women are considered patients at risk for pulmonary aspiration of gastric contents. The study aim was to evaluate the gastric antral cross-sectional area using ultrasound. Method: In this prospective study, 85 scheduled term pregnant women underwent gastric ultrasound. The outcomes were the measurement of the gastric antral cross-sectional area (main outcome), the estimated gastric volume, the incidence of pregnant women at risk for pulmonary aspiration, and the association between gastric antral cross-sectional area and clinical-demographic characteristics. Gastric antral cross-sectional area and gastric volume were compared according to body mass index <30 or ≥30. Results: The median (IIQ) for gastric antral cross-sectional area was 4 cm2 (2.8–6.3), for the estimated gastric volume it was 49.8 mL (33.7–87.2), and for the gastric volume estimated in mL.kg−1 it was 0.62 mL.kg−1 (0.39–0.95). The 95th percentile [95% confidence interval (CI)] of the gastric antral cross-sectional area and the estimated gastric volume were ≤10.3 cm2 (95% CI: 7.6–15.6) and 1.42 mL.kg−1 (95% CI: 1.20–2.64), respectively. The incidence of pregnant women at risk for pulmonary aspiration was 3.5% (CI: 3.5 (1.2–9.8)). There was a positive correlation between gastric antral cross-sectional area and weight, p < 0.001 and body mass index <0.001. Patients with a body mass index ≥30 had a gastric antral cross-sectional area and an estimated gastric volume greater than those with a body mass index <30, respectively, p < 0.01 and p < 0.02. Conclusion: Measuring the gastric antral cross-sectional area of pregnant women is feasible and easy. There was positive correlation between gastric antral cross-sectional area, body weight and body mass index. The estimation of gastric volume by measuring the gastric antral cross-sectional area can identify patients at risk for pulmonary aspiration. Obese patients had a gastric antral cross-sectional area and an estimated gastric volume greater than non-obese patients. Resumo: Justificativa e objetivos: As gestantes são consideradas pacientes de risco para aspiração pulmonar do conteúdo gástrico. O objetivo foi avaliar a área transversal do antro gástrico por meio de ultrassonografia. Método: Neste estudo prospectivo, 85 gestantes a termo agendadas foram submetidas à ultrassonografia do antro gástrico. Os desfechos foram a mensuração da área transversal do antro gástrico (desfecho principal), a estimativa do volume gástrico, a incidência de gestantes sob risco de aspiração pulmonar, a associação entre a área transversal do antro gástrico e características clínico-demográficas. A área transversal do antro gástrico e do volume gástrico foi comparada de acordo com o índice de massa corporal <30 ou ≥30. Resultados: A mediana (IIQ) da área transversal do antro gástrico foi 4 cm2 (2,8-6,3), do volume gástrico estimado 49,8 mL (33,7-87,2) e do volume gástrico estimado em mL.kg−1 de 0,62 mL.kg−1 (0,39-0,95). O percentil 95 [intervalo de confiança (IC) 95%] da área transversal do antro gástrico e do volume gástrico estimado foi ≤ 10,3 cm2 (IC 95%: 7,6-15,6) e 1,42 mL.kg−1 (IC 95%: 1,20-2,64), respectivamente. A incidência de gestantes sob risco de aspiração pulmonar foi de 3,5% (IC: 3,5 (1,2-9,8). Houve correlação positiva entre a área transversal do antro gástrico e peso, p < 0,001 e índice de massa corporal p < 0,001. As pacientes com índice de massa corporal ≥ 30 apresentaram maior área transversal do antro gástrico, e do volume gástrico estimado, do que as com índice de massa corporal < 30, respectivamente p < 0,01 e p < 0,02. Conclusão: A mensuração da área transversal do antro gástrico de gestantes é factível e fácil. A área transversal do antro gástrico correlacionou-se positivamente com peso e índice de massa corporal. A estimativa do volume gástrico através da mensuração da área transversal do antro gástrico pode identificar pacientes sob risco de aspiração pulmonar. As pacientes obesas apresentaram área transversal do antro gástrico e volume gástrico estimado maior do que as não obesas. Keywords: Ultrasound, Gastric antrum, Pregnant women, Cesarean section, Aspiration pneumonia, Palavras-chave: Ultrassonografia, Antro gástrico, Gestante, Cesariana, Pneumonia aspirativa